Label-free proteomic analysis of Xerophyta schlechteri leaf tissue under dehydration stress - Gabier, Hawwa (Department of Molecular and Cell Biology, 2021)
Most higher plants cannot withstand severe water loss, except for a small group of angiosperms called resurrection plants. They can survive severe water loss without the loss of viability by employing mechanisms that aid them in desiccation tolerance. Desiccation tolerance in resurrection plants is a complex and multifaceted phenomenon and allows the plant to implement various strategies for survival. The focus of this study was a label-free proteomic analysis of Xerophyta schlechteri, a monocotyledonous and poikilochlorophyllous resurrection plant, in response to desiccation. The study investigated some of the physiological, morphological and biochemical changes of X. schlechteri leaf tissue in response to dehydration followed by proteomic analyses using a spectral counting approach. The differentially expressed proteins were identified and quantified and then subjected to gene ontological analyses to identify relevant biological processes involved in desiccation tolerance. The proteomic data was finally correlated to and validated using metabolomic analyses. X. schlechteri was subjected to a controlled dehydration stress treatment, in which changes in the relative water content (RWC) of leaf tissues, the associated changes in processes outlined above and further expanded on below, were determined. Three physiological stages were tentatively identified, namely, the early response to drying (ERD) which represents ~ 80 - 70% RWC (1.61 gH2O g ̄ˡ dwt -1.5 gH2O g ̄ˡ dwt), a mid-response to drying (MRD) represented by ~ 60 - 40% RWC (1.5 gH2O g ̄ˡ dwt -1.0 gH2O g ̄ˡ dwt) and a late response to drying (LRD), represented by ~ 40 - 10% RWC (1.0 gH2O g ̄ˡ dwt - 0.5 gH2O g ̄ˡ dwt). Morphological changes in the late stages of drying were marked by loss of green chlorophyll, increased purple anthocyanin production and leaf folding along the midrib with the abaxial surface exposed to light. Chlorophyll content analyses showed a significant decrease in chlorophyll content in the dehydrated leaf tissue as compared to the fully hydrated state. Biochemical assays to measure the activity of enzymatic antioxidants, namely, ascorbate peroxidase (APX), catalase (CAT), glutathione reductase (GR) and superoxide dismutase (SOD) were done at selected RWC points. There was a significant increase in antioxidant enzyme activity for APX, CAT, GR and SOD in the dehydrated plant tissue. The label-free proteomics approach utilized, identified a total of 3125 unique proteins in the X. schlechteri leaf tissue across the dehydration treatment of which a combined 517 proteins were significantly differentially expressed in response to drying. Amongst the differentially expressed proteins, 253 proteins were upregulated, and 264 proteins were downregulated. This was followed by functional analyses and classification of gene ontologies using bioinformatics tools such as Blast2GO, MapMan and KEGG. This allowed the identification of certain biological processes and pathways involved in the X. schlechteri desiccation response. Key biological processes and molecular processes were differentially expressed across the drying stages, these included photosynthesis, cellular respiration and antioxidant activity, respectively. The proteomic analysis was complemented and validated using metabolomics approaches based on GC MS/MS and LC/MS. The abundance of specific sugars, sugar alcohols, fatty acids, organic acids, phytohormones and amino acids of X. schlechteri during desiccation were investigated. Sugars such as raffinose and sucrose are known to play a protective role in desiccation and were found to be abundant in MRD and LRD leaf tissue while, L-histidine, an amino acid which plays a critical role in plant growth, was found to be more abundant in LRD tissue as compared to MRD. The phytohormone abscisic acid, invoked in desiccation tolerance was found to be abundant at LRD and less abundant at ERD. The metabolomic data suggested that the regulation of metabolites was towards reducing possible toxic metabolites while increasing the expression of metabolites that help and protect plant cell integrity from the negative effects of desiccation. The use of a label-free proteomics approach complemented with metabolomics allowed the identification and validation of biological processes and pathways potentially involved in establishing desiccation tolerance in X. schlechteri. As far as we are aware, this is the first label-free proteomic analysis of X. schlechteri in response to dehydration.